Project P. 15 - Beavis, D.; Strank, R. H. D.; Leamon, T. B. (College of Aeronautics, 1964)
Summary System synthesis and analysis procedures were used to arrive at various conclusions about separation of functions, allocation of functions and, interface designs in a power station.